2014
DOI: 10.1111/insr.12034
|View full text |Cite
|
Sign up to set email alerts
|

Combining Probability Distributions by Multiplication in Metrology: A Viable Method?

Abstract: In measurement science quite often the value of a so-called 'output quantity' is inferred from information about 'input quantities' with the help of the 'mathematical model of measurement'. The latter represents the functional relation through which outputs and inputs depend on one another. However, subsets of functionally independent quantities can always be so defined that they suffice to express the entire information available. Reporting information in terms of such a subset may in certain circumstances re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Benefiting from those discussions, in [12] and [13] we showed that, in the metrological context, the effects of Borel's paradox are mainly revealed if further transformations of the quantities involved, designed as consistency checks, are carried out. For this reason, those inconsistencies were not noticed in our original analysis of the cosine error problem.…”
Section: The Original Proceduresmentioning
confidence: 74%
See 1 more Smart Citation
“…Benefiting from those discussions, in [12] and [13] we showed that, in the metrological context, the effects of Borel's paradox are mainly revealed if further transformations of the quantities involved, designed as consistency checks, are carried out. For this reason, those inconsistencies were not noticed in our original analysis of the cosine error problem.…”
Section: The Original Proceduresmentioning
confidence: 74%
“…To obtain the PDF f W (ω) by multiplication of distributions we can proceed in either of two ways [12,Sect. 3].…”
Section: Appendix 1: Aggregating Probability Distribu-tions By Multipmentioning
confidence: 99%
“…Since the same pair of likelihoods is used for successive updating in (20) and (21), logarithmic pooling of the priors followed by updating with the two likelihoods would lead to the same outcome as if (20) and (21) were directly logarithmically pooled. This property, which additive pooling does not have, is called 'external Bayesianity' [13] and was considered in a metrological context in [14]. However, given that non-informative priors normally have only a minor impact on the outcome, pooling them will in most cases be an unnecessary hassle.…”
mentioning
confidence: 99%